Bioactive compounds of fresh and dehydrated green pepper - Nascimento, Ana Marinho do; Costa, Franciscleudo Bezerra da; Silva, Jéssica Leite da; Araújo, Chintia Rodrigues de; Formiga, Anderson dos Santos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
Pepper Capsicum annuum L., belongs to the Solanaceae family, which contains approximately 31 species. Bioactive compounds also known as phytochemicals are chemical and biochemical components that are present in most fruits and vegetables. The objective of the present study was to verify if the bioactive compounds of the green pepper remain after being submitted to the drying process. The experiment was conducted in a completely randomized design with 2 treatments and 5 replicates. Green peppers were used from the (Economic Center of Supply Corporation) of the city of Patos, Paraíba. The peppers were packed in plastic boxes and transported to the Laboratory of Chemistry, Biochemistry and Food Analysis of the Federal University of Campina Grande, Campus Pombal. Where they were selected, washed and sanitized. After that, the minimum processing was done and the drying was carried out in a circulation oven at 60 ºC. At the end of the drying, the samples were crushed and sieved. After this process, the analyzes of ascorbic acid, chlorophylls, carotenoids, anthocyanin flavonoids and phenolic compounds. It was found that there was a significant difference between treatments. The bioactive properties of green pepper were not lost after the heat treatment. Some phytochemicals as ascorbic acid, carotenoids and phenolic compounds were concentrated. Therefore the loss of water during the drying process increased the concentration of the bioactive compounds of dehydrated pepper, the product obtained with this method exhibited high levels of phytochemicals, the use of drying may be an alternative to prolong the shelf life of the vegetable.